ISSUES OF ENVIRONMENTAL PROTECTION AND FORMATION OF ECOLOGICAL CULTURE OF PRIMARY CLASS STUDENTS - Nilufar Boynazarova (Scholar Express Journal, 2023)
This article talks about feedback on the formation of environmental education and culture, valuable information on the field of Ecology and Environmental Protection, Conservation of nature, rational use of Natural Resources, methods of educating students through methodological educational materials
Keywords: Ecological culture; ecological upbringing; ecology; ecological and delicate upbringing